Accounting for Islamic Fintech: Issues and Treatment (Case Study: Ammana Fintech) - Mukhlisin, Murniati; Farezi, Lalu Alpin (Journal of Islamic Contemporary Accounting and Business, 2025)
The main objective of this study to examine accounting treatment in Islamic FinTech company in Indonesia with reference of Islamic Accounting Standards - PSAK Syariah issued by The Indonesian Institute of Accountants. Methodology: This research conducts a case study of Ammana Fintek Syariah as the first Islamic FinTech in Indonesia registered in Indonesian Financial Services Authority. The finding shows that Ammana does not have a clear standard of accounting treatment as a FinTech company. Its reporting standard simply follows company’s discretion, following Practice Theory which has its own diverse motives and intentions to form its identity as Islamic FinTech company. In order to ensure the Islamic FinTech is always in the shariah corridor, thus Islamic accountability notion should be embedded within the company. The paper finds that Ammana Fintek made few adjustments on the existing PSAK Syariah to allow FinTech nature of transactions are accommodated. Reporting various Islamic contracts make the Islamic FinTech distinct from its conventional counterpart in dialectic relationship. Thus, separate guide on Islamic FinTech accounting is required soon or later considering potential Muslim market in Indonesia. Stakeholders of Islamic FinTech rely on digital reporting who demand timely and accurate information for making right decision. Contribution of this study is to expand Practice Theory not only in the social being relationship, human to human, but also structure to structure, in this case between Ammana Fintek and Ikatan Akuntan Indonesia (IAI).